2015
DOI: 10.1016/j.micres.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Pma1 is an alkali/alkaline earth metal cation ATPase that preferentially transports Na+ and K+ across the Mycobacterium smegmatis plasma membrane

Abstract: Mycobacterium smegmatis Pma1 is the orthologue of M. tuberculosis P-type ATPase cation transporter CtpF, which is activated under stress conditions, such as hypoxia, starvation and response to antituberculous and toxic substances. The function of Pma1 in the mycobacterial processes across the plasma membrane has not been characterised. In this work, bioinformatic analyses revealed that Pma1 likely contains potential sites for, Na(+), K(+) and Ca(2+) binding and transport. Accordingly, RT-qPCR experiments showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
1
10
0
1
Order By: Relevance
“…This optimal temperature is similar to the average temperature of the human body, which in turn is the natural host of M. tuberculosis. Similarly, the observed optimal pH (7.4) is close to neutrality, as well as the observed for other mycobacterial P-type ATPases [35][36][37]. Finally, CtpB displayed a concentration-dependent Cu + ATPase activity when the enzymatic reaction was supplemented with Cys at concentrations below 0.5 mM.…”
Section: Mycobacterium Smegmatis Cells Expressing M Tuberculosis Ctpsupporting
confidence: 78%
See 3 more Smart Citations
“…This optimal temperature is similar to the average temperature of the human body, which in turn is the natural host of M. tuberculosis. Similarly, the observed optimal pH (7.4) is close to neutrality, as well as the observed for other mycobacterial P-type ATPases [35][36][37]. Finally, CtpB displayed a concentration-dependent Cu + ATPase activity when the enzymatic reaction was supplemented with Cys at concentrations below 0.5 mM.…”
Section: Mycobacterium Smegmatis Cells Expressing M Tuberculosis Ctpsupporting
confidence: 78%
“…For example, recombinant M. smegmatis cells overexpressing the putative M. tuberculosis cadmium transporter CtpG tolerate high doses of Cd 2+ compared with non-recombinant mycobacterial cells [36]. Similarly, M. smegmatis homologously expressing the putative alkali/alkaline earth cation P-type ATPase transporter Pma1 tolerates toxic concentrations of Na + , K + , and Na + /K + ions [37]. Regarding P-type ATPases associated with copper transport, we previously reported that mycobacterial cells expressing the putative M. tuberculosis CtpA, a P-type ATPase copper transporter, grow approximately twofold more than non-recombinant cells in the presence of toxic copper concentrations (from 1 to 4 mM), suggesting a possible role of CtpA in copper detoxification in mycobacteria [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ATPase activity of the plasma membrane vesicles was measured according to the Fiske-Subbarow method with modifications, as previously described [19, 20, 46]. Enzymatic reactions (final volume 50 μL) were performed in 96-well plates using 10 μg of protein in reaction buffer (3 mM MgCl 2 , 10 mM MOPS, pH = 7.4) and supplemented with 0.02 % Brij-58, 0.29 mM Ca 2+ and 0.25 mM EGTA (final concentrations) to control the amount of free calcium.…”
Section: Methodsmentioning
confidence: 99%